Real estate infrastructure financing in Ghana: Sources and constraints. (December 2015) - Owusu-Manu, D.; Edwards, D.J.; Badu, E.; Donkor-Hyiaman, K.A.; Love, P.E.D.
Abstract: Finance represents a major barrier to real estate development in Ghana and constraints responsible remain unknown. In order to gain insight into this important social/economic issue, a positivist tradition of thinking via the survey approach sought to uncover, explain and rank these constraints using the Relative Importance Index. A total of 53 questionnaires were distributed to real estate developers within the Kumasi Metropolis of Ghana. The survey reveals that real estate developers predominantly use debt financing including short-term bank loans, mortgages and hire purchase. Finance is constrained by five main factors: i) legislation; ii) macroeconomic barriers; iii) collateral barriers; iv) inadequate risk assessment and diversification mechanisms; and v) a dearth of financial mobilization mechanisms. This paper provides a practical reference for the targeting of policy interventions to overcome these constraints and to catalyse the development of finance for real estate infrastructure delivery. The work is also useful to the Government, banks and capital market regulators who seek to develop the capital market to provide appropriate financing options. These options may include real estate investment trusts (REITs) and risk reduction/diversification platform via derivatives. Future research is proposed which seeks to explore practical innovations in designing tailor-made real estate financing options that meet the needs of real estate developers. Highlights: Sources and constraints of real estate finance for housing development in Ghana are identified. Debt financing including short-term bank loans, mortgages and hire purchase are mostly used. Factors constraining finance are identified. Implications for policy development are identified and discussed.